Comparative analysis of the characteristics of intuition of individuals with mathematical and humanitarian orientation - Alina Lobanova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article presents the results of empirical research of intuitionin humanities and mathematics individuals. On the basis of comparative analysis, the commonand different features are discovered in the two groups, taking into consideratin the characteristics of the thinking processes.
Keywords: intuition; intuitiveability; comparative analysis; forecasting ability; thinking processes